2015
DOI: 10.1007/s10886-015-0663-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cattle-Derived Volatiles that Modulate the Behavioral Response of the Biting Midge Culicoides nubeculosus

Abstract: Identification of host-derived volatiles is an important step towards the development of novel surveillance and control tools for Culicoides biting midges. In this study, we identified compounds from headspace collections of cattle hair and urine that modulate the behavioral response of Culicoides nubeculosus, a research model species with a similar hostrange as the vectors of Bluetongue disease and Schmallenberg disease in Europe. Combined gas chromatography and electroantennographic detection (GC-EAD) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 55 publications
3
24
0
6
Order By: Relevance
“…1-Octen-3-ol is a well-characterized mammalian kairomone (Pickett et al 2010 ), which is known to attract various hematophagous insects, including tsetse flies (Torr 1990 ; Vale and Hall 1985 ) and mosquitoes (Kline et al 1994 ; Takken and Kline 1989 ). As was observed for decanal, C. impunctatus were more attracted to traps with a low release rate of racemic 1-octen-3-ol, as previously shown in both laboratory and field studies (Bhasin et al 2000 ; Blackwell et al 1996 ; Isberg et al 2016 ) of C. impunctatus and C. nubeculosus . While this study analyzed the effect of racemic 1-octen-3-ol on attraction of C. impunctatus , other studies on both biting midges and mosquitoes imply that it is the ( R ) - enantiomer that is important for attraction (Harrup et al 2012 ) and for some species even repellence (Pingxi et al 2015 ).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…1-Octen-3-ol is a well-characterized mammalian kairomone (Pickett et al 2010 ), which is known to attract various hematophagous insects, including tsetse flies (Torr 1990 ; Vale and Hall 1985 ) and mosquitoes (Kline et al 1994 ; Takken and Kline 1989 ). As was observed for decanal, C. impunctatus were more attracted to traps with a low release rate of racemic 1-octen-3-ol, as previously shown in both laboratory and field studies (Bhasin et al 2000 ; Blackwell et al 1996 ; Isberg et al 2016 ) of C. impunctatus and C. nubeculosus . While this study analyzed the effect of racemic 1-octen-3-ol on attraction of C. impunctatus , other studies on both biting midges and mosquitoes imply that it is the ( R ) - enantiomer that is important for attraction (Harrup et al 2012 ) and for some species even repellence (Pingxi et al 2015 ).…”
Section: Discussionsupporting
confidence: 80%
“…Addition of phenol, 4-methylphenol, 3-propylphenol and 2-ethylhexanol, identified in air entrainments of cattle urine (Isberg et al 2016 ), to traps baited with CO 2 increased trap captures of C. impunctatus . The results obtained for phenol, as well as 4-methylphenol, agree with those observed for C. nubeculosus in the laboratory (Isberg et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon dioxide (CO 2 ), a general behavioral activator and attractant for many blood‐feeding insects, has been utilized for biting midge surveillance in the US (Smith and Mullens 2003). Addition of the kairomone 1‐octen3‐ol, expired from the breath of ruminants (Hall et al 1984), to CO 2 , has been found to improve numbers of biting midges caught in the UK, mainland Europe, the US, and Australia (Takken and Kline 1989, Kline et al 1994, Ritchie et al 1994, Bhasin et al 2001, Harrup et al 2012, Isberg et al 2016). UV light traps are widely used for capturing Culicoides and have been suggested as the gold standard for biting midge surveillance even though they may not accurately reflect biting rates on host animals (Carpenter et al 2008, Gerry et al 2009, Viennet et al 2011).…”
Section: Introductionmentioning
confidence: 99%